Slope reduction osteotomy decreases ACL graft forces and reduces anterior tibial translation under axial load - a biomechanical study. Issue 6 (28th June 2019) - Imhoff, Florian B.; Mehl, Julian; Obopilwe, Elifho; Imhoff, Andreas; Beitzel, Knut
Aims and Objectives: To perform an anterior closing wedge osteotomy by 10° for slope reduction and investigate the effect of axial load and anterior drawer on forces on ACL graft, strain and femoro-tibial kinematics in a native, ACL-deficient and reconstructed knee. Materials and Methods: Ten cadaveric knees with an increased native slope were selected for this study based on CT meas-urements. An anterior closing-wedge osteotomy was performed by 10° and fixed with an external fixator. Tibial axial load (200 N, 400 N) was applied, while the tibial side was mounted on a free mov-ing X-Y-table with open rotation in 30° of knee flexion. Additionally, an anterior drawer (134 N) was performed with and without axial load (200 N). Specimens underwent native testing, cut ACL, and reconstructed ACL with a standardized quadruple semi-t/gracilis-allograft. Each condition was ran-domly tested with native slope and reduced slope. Change of forces on ACL-graft (attached load-cell) and strain on native ACL (via DVRT) were recorded. Throughout testing, 3D motion tracking captured anterior tibial translation (ATT) and rotation versus the fixed femur. Results: Preoperative, specimens showed an averaged lateral and medial slope of (average ±SD) 10° ± 1.4°, and age 48.2 ± 5.8years. Slope reduction significantly decreased forces on ACL graft by 17% (p=0.001) at 200 N and by 33% (p=0.0001) at 400 N of axial load. Furthermore, ATT was significantly decreased after slope reduc-tion in native (p=0.01), cut (p=0.005), and ACL-graft (p=0.01) status. Strain in native ACL de-creased by 9.7 ± 0.13% (p<0.0001) after slope reduction without any load. However, anterior drawer without axial load maintained significantly higher anterior tibial translation (native-pre 4.12 ± 0.65 mm vs. native-post 5.82 ± 1.51 mm, cut-ACL-pre 9.35 ± 1.57 mm vs cut-ACL-post 12.0 ± 3.53 mm, ACL-recon-pre 4.60 ± 0.97 mm vs. ACL-recon-post 5.73 ± 1.45 mm) and significantly higher forces on ACL graft (p=0.0006) after osteotomy. When axial load was combined with anterior drawer no significant change on ATT after osteotomy was observed. Rotational analysis did show a significant effect in the ACL cut condition due to slope correction. Overall, native and reconstruct-ed ACL showed the same tibial kinematics throughout testing. Conclusion: In general, osteotomy lowered ACL graft force and ACL strain when the joint was axially loaded. Anterior tibial translation was reduced even in an ACL deficient knee. When anterior drawer was performed without axial load, ATT was higher after slope reduction in every condition.